Legal Counseling Regarding The Formation of Village Regulations in East Tanjung Jabung District - suwarsono, Ribut; Kurniawan, Kurniawan; haeran, Haeran; Marwendi, Reza Okva; Abidin, Zaenal; Ruswadi, Silvina Dwi (CV. Zabags Qu Publish, 2023)
This extension activity was carried out in Catur Rahayu Village with the consideration that if we look at the development of the formation of village regulations, there are still many obstacles faced, namely limited human resources. The aim of the service is to provide legal understanding regarding the formation of village regulations in Catur Rahayu Village, Dendang District, East Tanjung Jabung Regency. The service method used is legal education to the community, especially to the Catur Rahayu Village government and the Catur Rahayu Village BPD. Findings from the implementation of this activity revealed that there were many problems in the capacity to form village regulations, this had an impact on the administration of government which was only based on ordinary government management, without any breakthrough in the formation of village regulations which became the basis for innovation in developing the development of Catur Rahayu Village